Alterations of phenotype, physiology, and functional substances reveal the chilling-tolerant mechanism in two common Olea Europaea cultivars - Jiang, Chenkai; Hu, Wenjun; Lu, Hongling; Chen, Lin; Niu, Erli; Zhu, Shenlong; Shen, Guoxin (Frontiers in Plant Science, 2023)
Olive suffers from cold damage when introduced to high-latitude regions from its native warm climes. Therefore, this study aims to improve the adaption of olive to climates in which it is cold for part of the year. The phenotype, physiological performance, nutrient content, and gene expression of olive leaves (from two widely planted cultivars) were examined after cultivation in normal and cold stress conditions. The results showed that the cold-tolerant cultivar possessed stronger photosynthesis efficiency and higher anti-oxidase activity after cold treatment than the cold-sensitive cultivar. Alteration of gene expression and metabolites in the amino acid metabolism, glycerolipid metabolism, diterpenoid biosynthesis, and oleuropein metabolism pathways played an important role in the cold responses of olive. Furthermore, the construction of the network of genes for ubiquitination and metabolites suggested that polyubiquitination contributes most to the stable physiology of olive under cold stress. Altogether, the results of this study can play an important role in helping us to understand the cold hardiness of olive and screen cold-resistant varieties for excellent quality and yield.